2017
DOI: 10.1002/mbo3.528
|View full text |Cite
|
Sign up to set email alerts
|

Use of multiple‐locus variable‐number of tandem repeats analysis (MLVA) to investigate genetic diversity of Salmonella enterica subsp. enterica serovar Typhimurium isolates from human, food, and veterinary sources

Abstract: Salmonella enterica subspecies enterica serovar Typhimurium is the most common zoonotic pathogen in Bulgaria. To allow efficient outbreak investigations and surveillance in the food chain, accurate and discriminatory methods for typing are needed. This study evaluated the use of multiple‐locus variable‐number of tandem repeats analysis (MLVA) and compared results with antimicrobial resistance (AMR) determinations for 100 S. Typhimurium strains isolated in Bulgaria during 2008–2012 (50 veterinary/food and 50 hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(55 reference statements)
1
4
0
1
Order By: Relevance
“…On the other hand, STTR10 and ST8 locus were absent in many strains (46.6% and 48.8%, respectively). Our results were in concordance with results obtained by other authors, as it has been described how STTR10 is the locus with the highest percentage of absence, but also ST8 has been shown to be absent in many strains [33,37]. In our study, 33.3% of S. Typhimurium isolates were dominated by 7 frequent MLVA profiles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, STTR10 and ST8 locus were absent in many strains (46.6% and 48.8%, respectively). Our results were in concordance with results obtained by other authors, as it has been described how STTR10 is the locus with the highest percentage of absence, but also ST8 has been shown to be absent in many strains [33,37]. In our study, 33.3% of S. Typhimurium isolates were dominated by 7 frequent MLVA profiles.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, some identical MLVA types were found in both human and poultry isolates, indicating a possible route of transmission [37]. The study of the most frequent alleles obtained from the isolates of the different origins and the higher discriminatory index (DI), showed that ST6 was the loci with highest discriminatory index, and it may be of potential use for source attribution.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Typhimurium isolates obtained from humans than from non-human isolates. The ACSSuT is the typical resistance pattern factors of the DT104 (Adhikari et al, 2010; Mateva et al, 2018). The MDR S .…”
Section: Discussionmentioning
confidence: 99%
“…The differences in antimicrobial usage in humans and animals have resulted in different susceptibility profiles being observed in isolates of the same species depending on the host (Mateva et al., 2018; McManus et al., 2015). This was not found to occur for any of the ionophores tested against a range of MRSA isolates of human and veterinary origin.…”
Section: Discussionmentioning
confidence: 99%